ESCOLA DE TEMPO INTEGRAL: UMA ESCOLA DIFERENTE OU A ESCOLA QUE FAZ A DIFERENÇA? - Almeida, Denise de (2007)
The aim of this work is to describe the present proposal of the Full Time School in the State of São Paulo, to investigate and evaluate its implantation in a State Public School in Bertioga city in the year of 2006. It is a descriptive-analytical research of the implantation and Proposal Process of the Full Time School , considering some programs and projects introduced in earlier decades in the State of São Paulo, and other Brazilian States. The data was collected by the analysis of documents related to the proposal and by the observation of a researcher-member who took part in the implantation process of the Full Time School at the investigated school. The results describe the guideline legislation, the philosophic source (origin), general guidelines, curricular organization, working hours, daily teaching methodology, and possibilities and limits of the project in its implantation. Key words: Full Time School, Elementary Education, State Public School.(AU)